Dampak Perilaku Keuangan, Kecerdasan Spiritual, Pengetahuan Keuangan Dan Kebebasan Keuangan Terhadap Pengelolaan Keuangan Bagi Pelaku Bisnis - Yudhanta Sambharakresna; Anis Wulandari (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
The factors influencing the personal financial management of tourism entrepreneurs in Madura include financial behavior, spiritual intelligence, financial knowledge, and financial freedom. The sampling technique employed in this study is using convenience and purposive sampling. Method of documentation and observation are used to collect research data. This research utilizes several data analysis approaches, including multiple linear regression analysis, classical assumption testing, goodness-of-fit evaluation of regression models, descriptive analysis, as well as validity and reliability testing, in addition to hypothesis testing. The research findings show that financial behavior, spiritual intelligence, financial knowledge, and financial freedom significantly and positively influence one's personal financial management